Algorithmic trading and intra-industry information transfer - Zhang, Xiaori; Jiang, Christine; Young, Danqing (Review of Accounting Studies, 2026)
We examine the role of algorithmic trading in transmitting intra-industry information. Using a comprehensive U.S. sample, we find that algorithmic trading amplifies the stock price reactions of non-announcing firms to the earnings announcements of industry peers that report earlier in the same fiscal quarter. Further analyses reveal that sector exchange-traded funds serve as an important channel through which algorithmic trading facilitates the diffusion of industry information. Moreover, the effect of algorithmic trading strengthens when peers’ information is more relevant to the focal firm and of higher reporting quality. Finally, our evidence suggests that these effects reflect enhanced price discovery rather than temporary overreaction. Overall, our findings illuminate the informational role of algorithmic trading and its implications for market efficiency.